Soft Drink Consumption Pattern and Diabetes Mellitus Knowledge Level in Adolescents - Wahyudi, Wahyudi; Barus, Nency Utami Br; Andhani, Intan; Billa, Nurna; Wahyuni , Raduwi; Simatupang , Ahmad Shiddiq (Yayasan Ahmad Mansyur Nasirah, 2024)
Diabetes mellitus (DM) is a disease that develops due to impaired insulin production or function, which causes blood sugar levels to exceed normal limits. Adolescents are very vulnerable to DM because of their low level of DM knowledge and excessive soft drink consumption patterns. The aim of this research is to describe soft drink consumption patterns and the level of DM knowledge among adolescents in Medan Johor District. This research design with a quantitative approach involving 114 teenagers in the Medan Johor area as respondents. Data is collected through a questionnaire that has been validated by experts and for efficiency, the questionnaire is distributed via Google Form. The results of this study show that the majority of respondents (82 teenagers, 71.9%) consume soft drinks 1-2 times/week. The majority of respondents in this study showed a very good knowledge (70 teenagers, 61.4%). This research concludes that teenagers in Medan Johor have very good knowledge regarding DM and consume soft drinks in moderate amounts. It is recommended that future studies examine the effectiveness of educational interventions in reducing soft drink consumption and increasing diabetes knowledge among adolescents.